The Correlation Between The Level of Knowledge of Traders With Rhodamine B Content in Snack Sauce Around Muhammadiyah University of Surakarta - Jenita Berlian Nindyasari; Rezania Asyifiradayati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Food producers or sellers still useives such as prohibited dyes such as rhodamine B dye are still oeir products more attractive. There needs to be more traders' knowledge of the impact of using rhodamine B dye as a food additive. This research aims to determine the relationship between traders'ders' knowledge levehodamine B content in chili snacks around the Muhammadiyah University Surakarta campus. This research is quantitative research with an analytical observational research design with a cross-sectional approach. This research was conducted around the Muhammadiyah University Surakarta campus from October to November 2023. The population in this study was 40 traders. The sample in this research was 36 traders, determined using non-probability sampling techniques. A total of 36 sauce samples were tested using the Rhodamin Test Kit which was carried out at the Microbiology Laboratory of Muhammadiyah University, Surakarta. Data analysis using the Fisher Exact test processed with SPSS version 16 software. The results of identifying the rhodamine B content in 36 sample snack sauces around the Muhammadiyah University campus showed that two sauce samples were positive for containing rhodamine B, and there was no relationship between the level of knowledge and the rhodamine content B on chili snacks around the Surakata Muhammadiyah University campus (p-value=1.000). It is recommended to increase traders' understanding of applicable food safety regulations and standards and continue to update information regarding ingredients that can endanger consumer health. Keywords: Rhodamine B levels, Sauce, Knowledge, Traders